Miguel Artola Blanco. El fin de la clase ociosa. De Romanones al estraperlo. Madrid, Alianza, 2015, 312 págs., ISBN: 978-84-206-9344-6. - Inarejos Muños, Juan Antonio (Investigaciones de Historia Económica, 2019)
Sin resumen